2019
DOI: 10.1038/s41598-019-51632-9
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Glucan, Water Dikinase Affect Starch Degradation and Gametophore Development in the Moss Physcomitrella patens

Abstract: The role of starch degradation in non-vascular plants is poorly understood. To expand our knowledge of this area, we have studied this process in Physcomitrella patens. This has been achieved through examination of the step known to initiate starch degradation in angiosperms, glucan phosphorylation, catalysed by glucan, water dikinase (GWD) enzymes. Phylogenetic analysis indicates that GWD isoforms can be divided into two clades, one of which contains GWD1/GWD2 and the other GWD3 isoforms. These clades split a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Mutations in Arabidopsis Starch Synthase III were found to increase enzyme expression level and its activity [57]. Numerous studies documented that mutations in gene resulted in increased enzyme activity [39,58]. In the present study, molecular simulation results revealed that these mutations are favoring the bonding between the enzyme and its cofactor by stabilizing the structure, decreasing the binding free energy, and increasing its binding site residues.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Mutations in Arabidopsis Starch Synthase III were found to increase enzyme expression level and its activity [57]. Numerous studies documented that mutations in gene resulted in increased enzyme activity [39,58]. In the present study, molecular simulation results revealed that these mutations are favoring the bonding between the enzyme and its cofactor by stabilizing the structure, decreasing the binding free energy, and increasing its binding site residues.…”
Section: Discussionmentioning
confidence: 47%
“…Contrarily, quinclorac resistance in E. phyllopogan might solely depend on ethylene biosynthesis inhibition rather than cyanide degradation [38]. However, it is a fact that mutations can increase enzyme activity [39]. β-CAS mainly depends upon pyridoxal phosphate (PLP) for its activity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Two copies of the GWD gene were also observed in some angiosperm families, suggesting a divergence in function between GWD1 and GWD2 paralogs of these species. A different functional evolution may exist regarding PWD, another paralog of GWD, as described [ 2 ], but not the focus of current study. In M. esculenta , GWD2 and the other GWD isoforms were implicated by Zhou et al [ 45 ] in storage starch degradation, due to increased expressions during post-harvest physiological deterioration where its activity was linked to seed development in A. thaliana and not the degradation of transitory starch at night [ 8 ].…”
Section: Discussionmentioning
confidence: 98%
“…The plastid-localized alpha-glucan water dikinase ( GWD ) gene is encoded by the nuclear genome and its products catalyzes reactions responsible for starch phosphorylation, an essential step in the de novo biosynthesis of this polysaccharide [ 1 ]. Generally, two plastidial isoforms of GWD; GWD1 (EC 2.7.9.4) and phosphoglucan water dikinase (PWD) or GWD3 (PWD; EC 2.7.9.5) have been identified in most plants [ 2 ]. The dikinase mechanism of GWD and PWD involve autophosphorylation of the catalytic histidine by the β-phosphate of ATP, and the transfer of β-phosphate from the stable phosphohistidine to either the C3 or C6 position of the glucosyl residue of starch, while the γ -phosphate is transferred to water [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation